2019
DOI: 10.21638/spbu05.2019.205
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency as an Investment Instrument in a Modern Financial Market

Abstract: This paper considers the development of attractive strategies featuring cryptocurrency assets, considering their costs and potential risks. The object of analysis in this paper is cryptocurrency as an investment instrument. The main hypothesis of the research is that modern portfolio theory can be applied to cryptocurrency investments to design an investment portfolio with appropriate risk and profitability characteristics. The authors of the paper: (i) place cryptocurrencies in the context of modern financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
(15 reference statements)
1
17
0
3
Order By: Relevance
“…Modern portfolio theory tracing back to Markowitz (1952) suggests that investors can potentially maximize returns while even minimizing risks through selecting complementary assets with low price correlations. Later the findings of many studies that include Bernoulli (1954), Joyce and Vogel (1970), Markowitz (1999), Rubenstein (2002), and Saji (2014) lend support to the validity of Markowitz (1952). Financial assets like stocks show very close correlations during significant volatility, and their relations appear to be low under normal market conditions (Cao et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Modern portfolio theory tracing back to Markowitz (1952) suggests that investors can potentially maximize returns while even minimizing risks through selecting complementary assets with low price correlations. Later the findings of many studies that include Bernoulli (1954), Joyce and Vogel (1970), Markowitz (1999), Rubenstein (2002), and Saji (2014) lend support to the validity of Markowitz (1952). Financial assets like stocks show very close correlations during significant volatility, and their relations appear to be low under normal market conditions (Cao et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…However, Corbet et al (2018) made some interesting reviews on the role of cryptocurrencies as a credible investment asset class and as a valuable and legitimate payment system. As the value of cryptocurrencies is measured in terms of fiat currency, which fluctuates widely in markets, one should view cryptocurrencies more like investment assets than money itself (Saksonova & Kuzmina-Merlino, 2019). Indeed, the volatile behavior of the prices of cryptocurrencies makes them more a purely speculative asset than a new type of money (Glaser et al, 2014;Baur et al, 2018).…”
Section: Literature and Hypotheses Developmentmentioning
confidence: 99%
“…It has been shown that embracing digital capabilities and orientation to improve service delivery and customer integration increases the value of the products and services they offer, while increasing the long-term profitability [27][28][29]. In addition, scientists noted the positive impact of digitalization on revenue growth, cost reduction, financial performance, and sustainability [56][57][58][59]. Digital transformation increasingly requires SMEs to strive to achieve environmental sustainability goals [56].…”
Section: Digital Transformation As a Mediator Of Economic Sustainability Of Smesmentioning
confidence: 99%
“…Weiyi Liu, 2018 yılında Finance Research Letters dergisinde yayınlanan "Portfolio Diversification Across Cryptocurrencies" adlı çalışmada (Liu, 2018) (Saksonova & Kuzmina-Merlino, 2019). "The Impact of Cryptocurrency on the Efficient Frontier of Emerging Markets" adlı çalışmada ise, Bitcoin içeren portföylerin etkin sınır içerisinde yer aldığı gözlemlenmiştir.…”
Section: öNcü and Ektikunclassified